Burenko T. M. Psychologic ground for English apology - Burenko T. M. (Philological Treatises, 2020)
The article analyses the constituents of psychologic ground for apology (guilt, shame, conscience and politeness norms ) on the English language material. A conclusion is drowed that speech act of apology is used to minimize or neutralize possible offence.